Evaluation of the protective efficacy of six major immunogenic proteins of Mycoplasma Synoviae - Han, Shuizhong; Wang, Ying; Chang, Wenchi; Wang, Lizhen; Fang, Junyang; Han, Jingjing; Hou, Xiaolan; Qi, Xuefeng; Wang, Jingyu (Frontiers in Veterinary Science, 2024)
Mycoplasma synoviae (MS) is a primary avian pathogen prevalent worldwide that causes airsacculitis and synovitis in birds. Vaccination is recommended as the most cost-effective strategy in the control of MS infection. Novel alternative vaccines are needed for eradicating and controlling MS infection in flocks. DnaK, enolase, elongation factor Tu (EF-Tu), MSPB, NADH oxidase and LP78 are the major immunogenic antigens of MS and are promising targets for subunit vaccine candidates. In the present study, genes encoding DnaK, enolase, EF-Tu, MSPB, LP78, and NADH oxidase were cloned and expressed in Escherichia coli. Enzyme-linked immunosorbent assay showed that the six recombinant proteins were recognized by convalescent sera, indicating that they were expressed during infection. Two injections of the six subunit vaccines induced a robust antibody response and increased the concentrations of IFN-γ and IL-4, especially rEnolase and rEF-Tu. The proliferation of peripheral blood lymphocytes was enhanced in all of the immunized groups. Chickens immunized with rEnolase, rEF-Tu, rLP78 and rMSPB conferred significant protection against MS infection, as indicated by significantly lower DNA copies in the trachea, lower scores of air sac lesions, and lesser tracheal mucosal thickness than that in the challenge control. Especially, rEnolase provided the best protective efficacy, followed by rEF-Tu, rMSPB and rLP78. Our finds demonstrate that the subunit vaccines and bacterin can only reduce the lesions caused by MS infection, but not prevent colonization of the organism. Our findings may contribute to the development of novel vaccine agents against MS infection.